RELATIONSHIP BETWEEN PREGNANT WOMEN'S HIGH-RISK AGE WITH THE PRETERM OF LABOR IN BIDAN PRAKTIK MANDIRI (BPM) BIDAN NANIK SUWATI, AMD. KEB, PUNGGING VILLAGE, MOJOSARI SUB-DISTRICT, MOJOKERTO DISTRICT - Siti Fithrotul Umami; Titiek Idayanti (Nurse and Health: Jurnal Keperawatan, 2018)
Background. High-risk age for pregnant women is < 20 or > 35 years, the possibility of a bad pregnancy / complications will increase, such as preterm labor. Premature birth is the main cause in almost 2/3 of births. Preterm labor is a labor that occurs in pregnancy between 28 - 37 weeks. The incidence in BPM Bidan Nanik Suwati, Pungging Village, Mojosari Sub-District, which is from 80 women giving birth, found 7 respondents experienced preterm labor including 4 (57.14%) aged <20 and> 35 years and 3 (42.86%) aged 20 - 30 years.Objectives. The purpose of this study was to determine the correlation between pregnant women's high-risk age with the preterm of labor in Bidan Praktik Mandiri (BPM) Bidan Nanik Suwati, Amd. Keb, Pungging Village, Mojosari Sub-District, Mojokerto District.Methods. The research method used is analytic correlation with a case control approach using research instruments in the form of secondary data. The sample technique used in this study was total sampling, so the sample of the study was all pregnant women of high-risk age in BPM Nanik Suwati, Pungging Village, Mojosari Sub-District at 68 respondents. The results of data collection were processed by chi-square statistical test (X2) with a significance distance of α = 0.05.Results. From the results of the study, almost half (31%) of respondents experienced preterm labor and most (69%) of respondents experienced term delivery. Shows a significant relationship between the age of high-risk pregnant women with the incidence of preterm labor with a value of P = 0.036.Conclusion. The factors that influence preterm labor, such as parity, frequency of ANC patients, and obstetric complications. Therefore, it should be recommended for mothers as much as possible not to become pregnant at a high-risk age, namely age <20 and> 35 years. Keywords:      High Risk Age, Pregnant Women, Preterm Labor Incidence.